Empowering Success: Exploring the Synergy Between Leadership, Motivation, and Work Environment - Parashakti, Ryani Dhyan; Maulidi, Dewi (SAN Scientific, 2025)
This study examines the individual and combined effects of transformational leadership, work motivation, and work environment on employee performance at PT Perusahaan Gas Negara Area Tangerang, a state-owned gas company in Indonesia. A quantitative causal associative design was used. This study provides empirical evidence on the relative contributions of leadership, motivation, and work context to performance in a critical utility setting, informing human resource development strategies that emphasize inspirational leadership practices, comprehensive motivation programs, and a supportive work environment. This article integrates established perspectives on leadership and motivation with operational indicators of the work environment in an under-examined organizational context in Indonesia, offering practical guidance for managers and policymakers in state-owned utilities. Managerial Implications: These findings highlight that managers at PT Perusahaan Gas Negara Area Tangerang should focus on strengthening transformational leadership practices through leadership development programs that emphasize vision, empathy, and innovation. The novelty of this study lies in its integrative approach, which simultaneously examines transformational leadership, work motivation, and the work environment as interrelated determinants of employee performance in Indonesia's state-owned energy sector, providing new empirical evidence from a context that has received limited scholarly attention.